Normal triglyceride concentration and the risk of diabetes mellitus type 2 in the general population of China - Guo, Rubing; Wei, Lianhua; Cao, Yongtong; Zhao, Wei (Frontiers in Endocrinology, 2024)
Introduction: Hypertriglyceridemia and its derivatives are independent predictors of diabetes mellitus type 2 (T2DM). However, the relationship between triglyceride concentrations within the normal range and the incidence of T2DM remains to be clarified. This study investigated the potential relationship between variations in plasma triglyceride levels within the normal range and T2DM onset using data from a longitudinal study of health and retirement in China.Methods: Between 2010 and 2016, we conducted a retrospective cohort study involving 36,441 individuals with normal triglyceride levels. Using a Cox proportional hazards regression model, we examined the connection between normal triglyceride levels and T2DM incidence. We employed this method with smooth curve fitting to investigate potential nonlinear associations. Subgroup analyses were performed based on age, sex, body mass index, smoking and drinking status, hypertension, and family history of diabetes.Results: A significant linear relationship was observed between normal triglyceride levels and the incidence of T2DM. The hazard ratio for T2DM in individuals with normal triglycerides was 1.81 (95% confidence interval: 1.39, 2.36); P<0.001). Kaplan-Meier analysis further demonstrated a prospective association between the higher tertiles of normal triglyceride levels and the development of T2DM (P<0.001). Subgroup analysis revealed a stronger positive correlation between normal triglyceride levels in females and the risk of T2DM.Discussion: An increase in triglyceride levels within the normal range is related to a continuous increase in the incidence of T2DM in the general population. These findings show that almost everyone can benefit from reducing triglyceride levels, further emphasizing the importance of lifestyle changes in the general population.The dataset used in this study was sourced from the DATADRYAD database (www.datadryad.org) that was originally published by Chen et al. The data for this study were derived from the primary research data of the article titled "Association of body mass index and age with incident diabetes in Chinese adults" (14) (Dryad, https://doi.org/10.5061/dryad.ft8750v). This work is licensed under a CC0 1.0 Universal (CC0 1.0) Public Domain Dedication license.